Concurrence of HOST to some conventional sperm quality parameters and seminal enzymes of Jersey bulls semen - GUPTA, SHRIYA; SINGH, MADHUMEET (The Indian Journal of Animal Sciences, 2019)
In this study, hypoosmotic swelling test (HOST) was correlated with sperm quality such as motility, acrosome integrity, morphological abnormality and seminal enzymes including AST, ALT and ALP. Results revealed positive concurrence of HOS test to motility and acrosomal integrity and negative correlation between ALP and ALT in both the freezable and nonfreezable ejaculates. Since the HOS test is quick, easy and inexpensive method so it can be deployed as routine semen assessment procedure in semen stations to differentiate between the freezable and non-freezable bull semen.